Dose-finding study of biapenem in complicated urinary tract infections - Kawada, Yukimichi (Japanese Journal of Chemotherapy, 1999)
To find the optimal dose of biapenem (BIPM), a new parenteral carbapenem, in the treatment of complicated urinary tract infections, we performed a randomized, prospective, well-controlled study using imipenem/cilastatin (IPM/CS) as the control drug. The subjects had complicated urinary tract infection with pyuria of at least 5 WBCs/HPF, bacteriuria of at least 104CFU/ml and an identifiable underlying urinary tract disease. Only hospitalized patients aged from 50 to 79 years without indwelling catheters were enrolled in the study. Patients were randomly assigned to receive either 150 mg b. i. d. of BIPM (group L), 300 mg b. i. d. of BIPM (group H) or 500 mg/500 mg b. i. d. of IPM/CS (group C) by intravenous drip infusion for 5 days. Overall clinical efficacy was evaluated on the basis of criteria proposed by the Japanese UTI Committee as “excellent”, “moderate” or “poor”. Excellent and moderate responses were obtained in 80.0% of 10 patients in group L, and in 100% of 11 patients in group H and 14 patients in group C. The differences were not statistically significant. The bacteriological eradication rates achieved were 85.7% of 14 strains in group L, 100% of 21 strains in group H and 94.1% of 17 strains in group C, with no statistically significant differences. Clinical adverse reactions were experienced in 10.0% of the 10 patients in group L, and in 0% of the 13 patients in group H and the 15 patients in group C, with no statistically significant differences. Clinical value also was not significantly different between the three groups. Based on the results obtained in this study, we concluded that the optimal dose of BIPM in the treatment of complicated urinary tract infections is 300 mg b. i. d.